The Economics of Oppression: Domestic Servitude in Uzma Aslam Khan’s The Story of Noble Rot - Hassan, Fatima; A/P Nadaswaran, Shalini; Aishah Osman, Sharifah (SARE: Southeast Asian Review of English, 2025)
This research paper examines gendered domestic servitude in the Pakistani social milieu through Uzma Aslam Khan’s debut novel The Story of Noble Rot, highlighting the subaltern subject positioning of female domestic workers within a deeply stratified society. It scrutinizes the contrasting lives of a maidservant and an affluent businessman’s wife to explore the rigid master-servant dynamic shaped by economic disparity and patriarchal control. The analysis delineates how patriarchal structures dictate women’s roles, showing that wealth does not always guarantee autonomy, nor does financial contribution ensure ascendancy within the household. The relationships Mrs. Masood and Malika hold, both with the men in their lives and with each other, emphasize the pervasive discrimination that continues to shape women’s lived experiences in contemporary Pakistani society. By focusing on the master-servant relationship and broader societal disparities, the paper underscores the structural inequalities that keep domestic workers in cycles of penury, limiting their social and financial mobility despite temporary shifts in power.